2021
DOI: 10.1080/21655979.2021.1952051
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an eleven-miRNA signature to predict the prognosis of endometrial cancer

Abstract: Endometrial cancer (EC) is the most common gynecological malignancy. Recent studies have uncovered miRNA acted a striking role in predicting the prognosis of multiple tumors. Over 500 EC samples were selected from the Cancer Genome Atlas (TCGA) database. Univariate, LASSO and multivariate Cox regression analysis were employed to screen out the prognosis-involved miRNAs. Kaplan-Meier (K-M) and time-dependent receiver operation characteristic (ROC) curves were conducted to reveal survival analysis and assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 46 publications
3
5
0
Order By: Relevance
“…In addition, targeting LOXL4 promotes growth, survival and migration of this tumor [ 53 ]. In the case of miR-363, Lu et al noted its overexpression in endometrial cancer, which is consistent with our results [ 54 ]. In turn, miR-363 also acts as a tumor suppressor in colorectal cancer [ 55 ] and gastric cancer [ 56 ].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, targeting LOXL4 promotes growth, survival and migration of this tumor [ 53 ]. In the case of miR-363, Lu et al noted its overexpression in endometrial cancer, which is consistent with our results [ 54 ]. In turn, miR-363 also acts as a tumor suppressor in colorectal cancer [ 55 ] and gastric cancer [ 56 ].…”
Section: Discussionsupporting
confidence: 93%
“…hsa-mir-3614 can directly target upstream genes to promote cancer cell proliferation and invasion, and its role in renal clear cell carcinoma and non-small-cell carcinoma has been confirmed [ 51 , 52 ]. Similar to our study, Lu et al also pointed out that has-mir-3614 is low-expressed in endometrial cancerous tissue [ 53 ]. A previous study had showed that the low-expression of has-mir-3616 contributes to triple negative breast cancer migration and invasion [ 54 ], and at the same time, low-expression of hsamir-3616 was also found to significantly reduce the survival rate of EC patients in this study ( p < 0.001), which may be related to the expression of target mRNA.…”
Section: Discussionsupporting
confidence: 91%
“…Some of the targets of its encoded miRNAs are tumor necrosis factor, interleukin-1 receptor-associated kinase 1, leukocyte Transcripts of interleukin 1-β, TNF receptor-related factor 6, and complement factor H. Thus, low expression of hsa-mir-146a can cause tumor cells to be unrecognized causing immune evasion and reducing inflammatory responses [ 51 ]. Both Shen et al and Pastrello et al have found hasmir-146a association with the early onset of familial breast and ovarian cancer and the passible mechanism is through BRCA1/2 mRNA expression regulation [ 52 , 53 ]. Low-expression of hsa-mir-3170 often leads to translational inhibition or instability of target mRNA, inducing tumor cell generation.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the survival curve showed that the area under the curve (AUC) was 0.978, showing favorable risk prediction performance, and thus can be used to guide personalized treatments of EC patients and add prognostic value to the current clinical system [38]. Wu [39] and Liu [40] also established a risk assessment model composed of 11 miRNAs, including miR-4758, miR-876, miR-142, miR-190b, hsa-miR-216, hsa-miR-363, hsa-miR-940, hsa-miR-1301, and hsa-miR-3614, according to the database. Functional enrichment analysis revealed that these miRNAs were correlated with the occurrence and development of cancer and could predict the overall survival rate of endometrial cancer.…”
Section: Cell-free Non-coding Rnamentioning
confidence: 99%